What is a Batey? Origins and Trajectories of an Antillean Concept - Kieslinger, Julia; Dohardt, Raphael; Jansen, Silke; Kordel, Stefan (Journal of Latin American Geography, 2024)
This article explores the meaning of the term “batey,” which can be broadly defined as a distinct type of settlement in the Dominican Republic, closely linked to sugar cane cultivation and transnational migration dynamics with Haiti. Drawing on historical documentation, we examine semantic changes in the term, from its pre-Columbian origins through the colonial period to the present. We also present contemporary emic perspectives on what constitutes a batey—views obtained from interviews with inhabitants of 28 Dominican bateyes. Additional information was drawn from (participant) observation in 96 bateyes. From this, we deduced the recent trajectories of bateyes, which fosters our understanding of the interrelated dynamics of rural development, intersecting forms of migration, e.g. domestic and transnational, and the impact of globalization on local communities, as well as the persistent impact of colonialism on local societies and economies. Furthermore, we address power imbalances by taking intoaccount postcolonial perspectives and giving voice to batey inhabitants and migrants. Our findings may serve as a point of departure for further research from a postcolonial perspective on the marginalization and stigmatization of settlements with transnational dynamics.<br
Keywords: Dominican Republic; Haiti; transnational spaces; postcolonial perspectives; socio- cognitive linguistics